Prevalence and factors associated with olfactory impairment among patients with acne treated with oral isotretinoin: a cross-sectional study - Kondo, Rogério Nabor; Miot, Hélio Amante [UNESP]; Frare, Elouise Zwirtes; Garcia, Ellen Cristine Duarte; Yamakami, Abner Hiraku; Fornazieri, Marco Aurélio (Elsevier, 2024)
Objective: This study aimed to investigate the prevalence and factors associated with olfactory dysfunction in individuals exposed to Isotretinoin (ISO) for the treatment of acne, using the University of Pennsylvania Smell Identification Test (UPSIT®). Methods: This cross-sectional study enrolled age and sex-matched patients with acne who were current users of oral ISO and unexposed controls without olfactory complaints. UPSIT® and a validated questionnaire (Nasal Obstruction Symptom Evaluation) were administered to evaluate nasal obstruction in patients exposed to ISO. Results: A total of seventy patients were recruited, with 35 in the exposed group and 35 in the unexposed group, consisting of 18 males and 17 females in each group, aged from 17 to 47 years. The prevalence of olfactory dysfunction was higher in the exposed group compared to the non-exposed group (62.9% vs. 17.1%), yielding a Prevalence Ratio (PR) of 3.7 (95% CI 1.9–7.1). However, no participants were categorized as anosmia or severe hyposmia and the majority of dysfunction was mild hyposmia compared to moderate hyposmia (51.5% vs. 11.4%). Among the exposed individuals, gasoline, orange, coffee, and wood exhibited the highest rates of identification errors (≥54%). Olfactory function demonstrated a negative correlation with treatment duration (p = 0.01), cumulative dose (p = 0.02), and nasal obstruction (p = 0.02). Conclusions: Olfactory dysfunction was more prevalent among ISO users, despite the patients being unaware of the disorder. Olfactory changes were correlated with treatment duration, cumulative dose, and nasal obstruction. Level of evidence: Level 4.
Keywords: Acne; Anosmia; Isotretinoin; Nasal diseases; Smell disorders